2017
DOI: 10.1007/s00701-016-3063-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audit effectively bridges the evidence-practice gap in chronic subdural haematoma management

Abstract: BackgroundPlacement of a subdural drain after drainage of chronic subdural haematoma (CSDH) has been shown to reduce the rate of recurrence in several randomised controlled trials (RCT). The most recently published RCT was from Cambridge, UK, in 2009. Despite class I evidence for the use of subdural drains, it is unclear whether these results have been translated into clinical practice. In this clinical audit we review the use of subdural drains in our institution before and after the publication of the 2009 R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Tailor et al [5] performed a retrospective study on burr-hole drainage of CSDH and found that the 6month reoperation rate was 8.1% (10/123) in the subdural drain group. Incision of the hematomas' inner membrane was not done, and 21.1% of cases were bilateral.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tailor et al [5] performed a retrospective study on burr-hole drainage of CSDH and found that the 6month reoperation rate was 8.1% (10/123) in the subdural drain group. Incision of the hematomas' inner membrane was not done, and 21.1% of cases were bilateral.…”
Section: Discussionmentioning
confidence: 99%
“…This condition has been treated by various surgical procedures such as burr-hole evacuation, twist-drill craniostomy, and craniotomy. However, all these procedures are associated with several complications including recurrence [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,17 However, numerous questionnaire surveys indicate that there is an evidencepractice gap in the usage of drains, as not all neurosurgeons place them regularly. 4,[18][19][20][21][22] Despite reported evidence supporting the benefits of drain placement, drain usage in everyday practice within the neurosurgical department of Helsinki University Hospital was arbitrary until, on April 1, 2017, consistent management of CSDHs with subdural drains was established in our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…The accompanying paper by Tailor et al from the King's College Hospital in London provides a unit-specific perspective regarding the post-trial dissemination and implementation phase [12]. The authors report that the use of drains increased from 17% to 35% in the post-trial period, but it was only until after a departmental presentation of the trial results in 2015 that drain utilisation increased to 75%.…”
mentioning
confidence: 99%